Opportunistic infections after conversion to belatacept in kidney transplantation. Issue 2 (7th February 2020) - Bertrand, Dominique; Chavarot, Nathalie; Gatault, Philippe; Garrouste, Cyril; Bouvier, Nicolas; Grall-Jezequel, Anne; Jaureguy, Maïté; Caillard, Sophie; Lemoine, Mathilde; Colosio, Charlotte; Golbin, Léonard; Rerolle, Jean-Philippe; et al.
Abstract: Background: Belatacept (bela) rescue therapy seems to be a valuable option for calcineurin inhibitor chronic toxicity in kidney transplantation. Nevertheless, the risk of infection associated with bela is not well reported. Methods: We report the rate of opportunistic infections (OPI) after a switch to bela in a multicentric cohort of 280 kidney transplant patients. Results: Forty-two OPI occurred in 34 patients (12.1%), on average 10.8 ± 11.3 months after the switch. With a cumulative exposure of 5128 months of bela treatment, we found an incidence of 0.008 OPI/month of exposure, and 9.8 OPI/100 person-years. The most common OPI was cytomegalovirus (CMV) disease in 18/42 OPI (42.9%) and pneumocystis pneumonia in 12/42 OPI (28.6%). Two patients presented a progressive multifocal leucoencephalopathy and two patients developed a cerebral Epstein–Barr virus-induced post-transplant lymphoproliferative disease. OPI led to death in 9/34 patients (26.5%) and graft failure in 4/34 patients (11.8%). In multivariate analysis, estimated glomerular filtration rate <25/mL/min/1.73 m 2 on the day of the switch and the use of immunosuppressive agents before transplantation were associated with the occurrence of OPI. We found a higher rate of infection-related hospitalization (24.1 versus 12.3/100 person-years, P = 0.0007) and also a higher rate of OPI (13.2 versus 6.7/100 person-years, P = 0.005) in the early conversion group (within 6 months). Conclusions: The risk of OPI is significant post-conversion to bela and may require additional monitoring and prophylactic therapy, particularly regarding pneumocystis pneumonia and CMV disease. These data need to be confirmed in a larger case–control study.